Tree mycorrhizal type regulates leaf and needle microbial communities, affects microbial assembly and co-occurrence network patterns, and influences litter decomposition rates in temperate forest - Tanunchai, Benjawan; Ji, Li; Schroeter, Simon Andreas; Wahdan, Sara Fareed Mohamed; Thongsuk, Katikarn; Hilke, Ines; Gleixner, Gerd; Buscot, François; Schulze, Ernst-Detlef; Noll, Matthias; Purahong, Witoon (Frontiers in Plant Science, 2023)
Tree mycorrhizal types (arbuscular mycorrhizal fungi and ectomycorrhizal fungi) alter nutrient use traits, leaf physicochemical properties, and thus affect leaf litter decomposition. However, little is known about how different tree mycorrhizal species affect the microbial diversity, community composition, function, and community assembly processes that govern leaf litter-dwelling microbes during leaf litter decomposition. In this study, we investigated the microbial diversity, community dynamics, and community assembly processes of nine temperate tree species, including broadleaved arbuscular mycorrhizal, broadleaved ectomycorrhizal, and coniferous ectomycorrhizal tree types, during leaf litter decomposition. Leaves and needles of different tree mycorrhizal types significantly affected the microbial richness and community composition during leaf litter decomposition. Leaf litter mass loss was related to higher sequence reads of a few bacterial functional groups, particularly N-fixing bacteria. Furthermore, a link between bacterial and fungal community composition and hydrolytic and/or oxidative enzyme activity was found.The microbial communities in the leaf litter of different tree mycorrhizal types were governed by different proportions of determinism and stochasticity, which changed throughout litter decomposition. Specifically, determinism (mainly variable selection) controlling bacterial community composition increased over time. In contrast, stochasticity (mainly ecological drift) increasingly governs fungal community composition. Finally, co-occurrence network analysis showed greater competition between bacteria and fungi in the early stages of litter decomposition and revealed a contrasting pattern between mycorrhizal types. Overall, we conclude that tree mycorrhizal types influence leaf litter quality, which affects microbial richness and community composition, and thus leaf litter decomposition.